(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
The hydrolysis of 3-cyano- and 3-carbethoxy-4,5-diphenyl-Δ3-butenolidеs in the presence of hydrochloric or sulfuric acids as well as in sodium hydroxide has been realized. It has been shown that 3-cyano-4,5-diphenyl-Δ3-butenolidе in the presence of hydrochloric acid either at 400C, or when boiled converts into 3-amido-Δ3-butenolidе, but in the presence of 30% sulfuric acid with quantitative yield by 3-carboxy-Δ3-butenolide is obtained. The latter when heated to 1700C undergoes decarboxylation with the formation of 4,5-diphenyl-Δ3-butenolidеs. 3-Carboxy-4,5-diphenyl-Δ3-butenolide is obtained also by hydrolysis of 3-carbethoxy-4,5-diphenyl-Δ3-butenolidе in the presence of sulfuric acid as well as 10% sodium hydroxide.